MEMBANGUN KESADARAN LINGKUNGAN SEJAK DINI MELALUI DESAIN POSTER KREATIF: EDUKASI MEMBUANG SAMPAH PADA TEMPATNYA BAGI SISWA SD ISLAM AL-RASYID PEKANBARU - Della Oktavinoarti; Fauziyah Afni; Saftika Wulandari; Muhamad Roihan AlAzhari (LPPM Universitas Awal Bros, 2026)
This Community Service Program aims to develop early environmental awareness among lower-grade elementary school students through a Visual Communication Design approach. The main issue faced by the partner school is the low awareness and habit of students in disposing of waste properly within the school environment. The program was implemented with second-grade students at SD Islam Al-Rasyid Pekanbaru using a participatory learning method that integrates environmental education and creative poster-making activities. The program stages included the delivery of environmental cleanliness education through visual media, followed by guided poster creation using basic visual communication design principles adapted to the cognitive characteristics of elementary school students. The results indicate an improvement in students’ understanding of proper waste disposal behavior, as reflected in active participation, the ability to recognize simple waste categories, and positive behavioral changes observed during the activity. In addition, the posters created by students function as sustainable educational media within the school environment. This program demonstrates that creative visual-based approaches in Visual Communication Design are effective tools for environmental education at an early age.